Preliminary characterization of β-decarboxylase activities in Staphylococcus carnosus 833, a strain used in sausage fermentation - Fadda, Silvina G. (2003)
In sausage, Staphylococcus carnosus increases the levels of methyl ketones which could arise from incomplete β-oxidation of fatty acids followed by a decarboxylation. The objective of this work was to characterize the β-decarboxylase activities in cell-free extract. By using different substrates, at least two kinds of β-decarboxylase activities were shown: an acetoacetate-like and an oxaloacetate-like. The first one leads to the production of ketones from ethylbutyryl acetate or acetoacetic acid. The activity was optimal at pH 6.0, stimulated by pyridoxal phosphate but ethylenediamine tetraacetic acid (EDTA), NaCl, iodoacetate and curing additives were inhibitory. The second decarboxylase activity leads to the production of pyruvic acid from oxaloacetic acid. This activity was optimal at pH 5.0 and stimulated by divalent ions and biotin.